2017
DOI: 10.1039/c7ra07731a
|View full text |Cite
|
Sign up to set email alerts
|

Study on non-isothermal crystallization behavior of isotactic polypropylene/bacterial cellulose composites

Abstract: Bacterial cellulose (BC) has great potential to be used as a new filler in reinforced isotactic polypropylene (iPP) due to its characteristics of high crystallinity, biodegradability and efficient mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…Recent results focus on applications in the area of packaging [149,150], water absorption [151] and supercapacitors [152,153], as well as optical devices [154][155][156][157][158][159][160]. In such applications, either BNC itself is reinforced by additives [161][162][163][164] or BNC serves as the reinforcing material, e.g., for synthetic polymers [165,166]. Another aim of current research is the enhancement of BNC properties to get softer and more flexible materials [167].…”
Section: Recent Developments In Bnc Materialsmentioning
confidence: 99%
“…Recent results focus on applications in the area of packaging [149,150], water absorption [151] and supercapacitors [152,153], as well as optical devices [154][155][156][157][158][159][160]. In such applications, either BNC itself is reinforced by additives [161][162][163][164] or BNC serves as the reinforcing material, e.g., for synthetic polymers [165,166]. Another aim of current research is the enhancement of BNC properties to get softer and more flexible materials [167].…”
Section: Recent Developments In Bnc Materialsmentioning
confidence: 99%
“…Caprylyl chloride (with the mass ratio of BC 30:1) was added dropwise into the system. After 7 h, the solid product of the system was washed with ethyl alcohol and deionized water to neutralize the product and dried in an air-oven for 12 h, and CO was obtained [30]. Under this condition, the substituting degree of CO was 2.32 [27].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our research group has reported the non-isothermal crystallization of the iPP/BC composites. Results show that the non-isothermal crystallization rates ascend in the order; the compatibility of iPP/BC composites and the cooling rate have great influence on the non-isothermal crystallization behavior of iPP/BC composites [30].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain high mechanical properties, improving the interfacial adhesion between SGF and polymer matrix is necessary and many efforts have been made . So far, maleic anhydride or glycidyl methacrylate as compatibilizer was used to graft PP which is general method to improve the interfacial adhesion between fibers and matrix . Sakai group found that lignin derivatives could improve the compatibility of PP and carbon fiber effectively.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] So far, maleic anhydride or glycidyl methacrylate as compatibilizer was used to graft PP which is general method to improve the interfacial adhesion between fibers and matrix. [19][20][21] Sakai group [22] found that lignin derivatives could improve the compatibility of PP and carbon fiber effectively. As a commonly used surface modification agent, silane agent generally consists of two parts: a hydrophilic group and an organophilic group.…”
Section: Introductionmentioning
confidence: 99%